PENINGKATAN KUALITAS PEMBELAJARAN KEAKSARAAN DASAR (FUNCTIONAL LITERACY) MELALUI PENDEKATAN KONSTRUKTIVISTIK DI SKB JAKARTA TIMUR - untung untung; Latang Latang; Fatmawati Gaffar (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2024)
The aim of this research is to improve the quality of functional literacy learning through a constructivist approach related to students' mastery of competencies, namely reading, writing, arithmetic and communicating in Indonesian. This action research was carried out in the functional literacy learning group "Cahaya Ilmu" under the guidance of the Community Learning Activity Center (PKBM) Bulukumba Regency. The research results show that students are motivated to learn if the learning material is integrated with skills education. They also study actively if the learning material suits their interests and needs based on the problems they experience every day. They are more confident in learning if their opinions are respected because generally they are adults. The application of constructivist learning strategies can improve the quality of learning in basic literacy learning groups both individually and as a group. The implication of this research is that the meaning of learning and active and creative learning can be achieved through a constructivist learning approach. However, the professionalism and creativity of tutors can be improved through training tutors in basic literacy education first, before they teach in study groups